Battle for the soul : Métis children encounter evangelical Protestants at Mackinaw Mission, 1823-1837 - Widder, Keith R. (Book collections on Project MUSE., 1999)
In 1823 William and Amanda Ferry opened a boarding school for Métis children on Mackinac Island, Michigan Territory, setting in motion an intense spiritual battle to win the souls and change the lives of the children, their parents, and all others living at Mackinac. Battle for the Soul demonstrates how a group of enthusiastic missionaries, empowered by an uncompromising religious motivation, served as agents of Americanization. The Ferrys'' high hopes crumbled, however, as they watched their work bring about a revival of Catholicism and their students refuse to abandon the fur trade as a way.